P119 Evolving surgical expertise and patient choice in pulmonary endarterectomy. (12th November 2019) - Babu, A; Ruggiero, A; Cannon, JE; Coghlan, G; Lordan, J; Howard, L; Jenkins, D; Johnson, M; Kiely, DG; Ng, C; Screaton, N; Sheares, K; et al.
Abstract : Background: Chronic thromboembolic pulmonary hypertension (CTEPH) is a two-compartment model characterized by the thrombofibrotic occlusion of proximal pulmonary arteries with secondary small vessel vasculopathy. Pulmonary endarterectomy (PEA) is the gold standard treatment for eligible patients although a proportion of patients with operable disease decline surgery. Those with distal lesions ineligible for PEA are managed medically, including consideration of balloon pulmonary angioplasty (BPA). Methods: Consecutive treatment-naïve patients discussed at the UK National PEA MDT and diagnosed with CTEPH between 2014 and 2017 were included. Haemodynamic, functional and patient-reported measures at time of MDT discussion were collected from patient records. Survival until July 2019 was recorded from a centralized national resource. Results: 787 patients were diagnosed with technically operable CTEPH with 77% proceeding to surgery. 66 patients were offered but declined PEA, of which 42 were treated with pulmonary vasodilators. Other patients with technically operable CTEPH did not undergo PEA due to limited disease distribution (n=46) or significant co-morbidities (n=67). There were 86 diagnoses of distal CTEPH, 73 received vasodilators and one-third underwent BPA (n=26). There were significant differences in age, baseline haemodynamics and patient-reported outcomes between those who underwent PEA, those offered but declining PEA and those with distal CTEPH, although functional status did not differ. Those offered but declining PEA were significantly older, had less severe haemodynamics and better self-reported functional status than those who underwent PEA. Only age (younger) and cardiac output (higher) were significantly different in those undergoing PEA compared to those with distal CTEPH. Three-year survival was lower in those who declined surgery or had distal CTEPH compared to those undergoing PEA but did not reach statistical significance (p=0.11) Conclusions: There has been an increase in operative intervention for CTEPH in the UK which likely reflects evolving surgical expertise. 1 Numbers offered but declining PEA are now lower, and with prognostically less severe disease, compared to previous cohorts making survival comparison difficult. 1 The use of medical therapies and BPA in the management of distal CTEPH has improved medium-term survival of those in this group to comparable with PEA.